THE IMPACT OF TURKISH CULTURE ON UZBEK PEOPLE - Toshpulatova Sarvinoz; Nurova Maftuna (TADQIQOTLAR, 2025)
Annotation: This article talks almost how Turkish culture has affected the conventions, dialect, instruction, design, and existence of Uzbek individuals. It examines the authentic foundation and the part of media, instruction, and tourism. The article too appears how youthful individuals in Uzbekistan are interfacing with Turkish patterns and values.